THE EFFECTIVENESS OF COAGULANTS AND FLOCCULANTS IN IMPROVING CLARIFIER WATER QUALITY: A CASE STUDY AT PT PERTA ARUN GAS, LHOKSEUMAWE - Rahmah, Maulidia; Mahrizal, Mahrizal; Asmara, Anjar Purba (Department of Chemistry Faculty of Science and Technology UIN Walisongo, 2025)
This study evaluated the effectiveness of coagulants and flocculants in improving clarifier water quality, with a focus on pH, iron (Fe) concentration, and turbidity levels. In accordance with Indonesia’s Ministry of Health Regulation No. 32/2017 on environmental health standards for water, clarifier water samples were analyzed before and after treatment. The results show that the treated water complied with the specified standards, with pH levels ranging from 6.5 to 8.5, Fe concentrations below 1 mg/L, and turbidity under 25 NTU. The application of aluminum sulfate as a coagulant and polymer as a flocculant effectively reduced Fe concentrations and turbidity while adjusting the pH to acceptable levels. These findings confirm the critical role of coagulation and flocculation in industrial water treatment processes and demonstrate their potential for enhancing water quality in clarifier systems.